Response of germination and early seedling growth of phog (Calligonum polygonoides) and khara lana (Haloxylon recurvum) to temperature and salinity - RATHORE, V S; SINGH, J P; NATHAWAT, N S; MEEL, B; BHARDWAJ, S (The Indian Journal of Agricultural Sciences, 2012)
Experiment was conducted to assess the effect of temperature and salinity on germination and seedling growth of C. polygonoides and H. recurvum. Seeds were incubated at five temperatures (15, 20, 25, 30 and 35 °C) with six NaCl concentrations (0,100, 200, 300, 400 and 500 mM) for H. recurvum and with seven NaCl concentrations (0, 25, 50, 100, 200, 300, and 400 mM) for C. polygonoides. The 20–25 °C temperature seems to optimum for germination and seedling growth of C. polygonoides and H. recurvum. Germination and seedling growth were inhibited by either an increase or a decrease in temperature from the optimal temperature. The C. polygonoides germinated up to 100 mM NaCl concentration, whereas H. recurvum germinated up-to 400 mM NaCl concentration under optimal temperatures. The 50 % reduction in seedling growth of C. polygonoides and H. recurvum was recorded with > 50 mM and 300 mM NaCl, respectively. The interaction effect of temperature and salinity on all measured variables was significant. Salinity- induced inhibition of germination and seedling growth was more at higher temperatures in both species. These results provide information pertaining to germination behaviour of species, and shows that in arid region, selection of suitable planting time and site must take into account both salinity and temperature.